(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
There are many architectural monuments in Uzbekistan that are part of the treasury of world culture. Historical centers of Khiva, Bukhara and Shakhrisabz, historical monuments of ancient Samarkand are included in the UNESCO list of "World Heritage", folklore ensemble of Boysun district is included in the list of "World Intangible Heritage".